Advanced digital technologies in financial and business management : unleashing the power of artificial intelligence, machine learning, blockchain, and the internet of things - Arora, Jyoti Batra, 1979-; Pathak, Nitish; Sharma, Neelam (Apple Academic Press, 2025)
This new book explores emerging new technologies for the development of business and finance sectors, to strengthen economic growth, and to facilitate the efficiency and creation of new and innovative business and finance management applications. The book covers state-of-the-art technologies such as artificial intelligence and big data analytics in fintech and finance, blockchain technology in the insurance industry, the use of AI and data science in tax administration, the growing use of 6G in industrial automation, quantum machine learning in finance, the merging of AI and blockchain in auditing, and more. Chapters explore the collaboration between humans and machines, the application of data science and artificial intelligence in the retail sector, and AI and data science in business services with a focus on enhancing efficiency and driving innovation.